2021
DOI: 10.3390/su13137406
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Smoke Extraction System for Atrium: A Numerical Study

Abstract: Smoke extraction systems, either static with natural ventilation, or dynamic with mechanical ventilation are required to keep smoke layer at high levels in many tall atria. It is observed that a design fire with high heat release rate (HRR) is commonly used for designing natural vents, but a low HRR is used for mechanical ventilation system. This will not produce a sustainable environment. There are no internationally agreed on design guides to determine the HRR in the design fire for different extraction syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…From the experiment results, the station atrium was beneficial for accumulating the smoke then exhausting it at the early stage. In previous studies, some scholars confirmed that a higher atrium could improve the efficiency of smoke extraction significantly [18,30,31]. Larger atrium space could strengthen the capacity for smoke storage, and also enhances the stack effect.…”
Section: Temperature Distributionmentioning
confidence: 93%
See 2 more Smart Citations
“…From the experiment results, the station atrium was beneficial for accumulating the smoke then exhausting it at the early stage. In previous studies, some scholars confirmed that a higher atrium could improve the efficiency of smoke extraction significantly [18,30,31]. Larger atrium space could strengthen the capacity for smoke storage, and also enhances the stack effect.…”
Section: Temperature Distributionmentioning
confidence: 93%
“…At 120 s after the ignition in Test 1 at station A, the production of smoke was steady. As shown in Figure 15, the clear smoke stratification formed vertically in the subway platform, owing to the comprehensive effect of smoke buoyance force [18,30,33]. High-temperature smoke would flow upward under the influence of the stack effect, and the smoke layer would change with the variation of the height between smoke and fresh air.…”
Section: Validation Of Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A design fire with high HRR such as 20 MW is commonly used for designing natural vents, but a low HRR such as 5 MW is used for mechanical ventilation system. A sustainable new hybrid design combining the advantages of static and dynamic systems is proposed [29], which could result in a lower smoke temperature and higher smoke layer interface height, indicating a better extraction design.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it provides the required rate of air changes in buildings [2]. For improving the thermal comfort of these buildings, Computational Fluid Dynamics analyses are very often developed and allow for consideration of some configurations for their daily and fire ventilation systems [3][4][5].…”
Section: Introductionmentioning
confidence: 99%